Komunitas Sepeda Gowes Menjadi Gaya Hidup Sehat(Pada Komunitas Sepeda Gowes Rumah Sakit Soeradji Tirtonegoro Klaten Atau Scck) - Al Anshori, Rosyid Fachrudin, Prof. Dr. Kumaidi, MA (2017)
The phenomenon bike functions of transportation is now a tool for fun, adventure, and maintain health. Healthy lifestyle is associated with health conscious behavior consistent as stop unhealthy behaviors such as smoking, alcohol consumption, or sedentary behavior; and practicing healthy behaviors such as regular exercise. The purpose of this study in to understand and describe how the cycling community into a healthy lifestyle.The method of collecting data in this study using interviews and observations.Informants in this study is a member of a community hospital gowes soeradji tirto negoro klaten or scck. The results of this study are the cycling community is made up of individuals who have reasons that vary according to their own perception, bias in the form of doromgan from the outside or from ourselves to meet the biological and psychological needs. Impact obtained by the many add friends, is capable of controlling foods, stop darimelakukan things that are damaging to health by pengalamna its members in the community, and the informant became motivated in cycling because there is the presence of friends sekomunitas. Keywords: bicycle, cycling community,lifestyle, a healthy lifestyle.